Instrumental and macroseismic data on processes in the focal zone of the Krivoy Rog earthquake on December 25, 2007. - B. G. Pustovitenko; V. E. Kulchitsky; A. A. Pustovitenko; A. M. Sklar (Геофизический журнал, 2010)
In this paper the results of the studies of kinematical and dynamic characteristics of seismic waves and source for tangible Krivorozhsky earthquake on 25.12.2007 are presented. The refined data about the depth of the earthquake hypocenter and shaking intensity distribution are quoted. For the first time for the earthquake of the territory of the Ukrainian Shield focus parameters are restored, namely: source mechanism, dynamic characteristics, seismic moment tensor components, parameters of tearing process. It is shown, that deformation of medium in focal zone was shearing, the sliding of rupture bands was "rough", the tearing process developed as directed from the bottom upward to the northwestern direction.. Identification of seismic events for the last 15 years around Krivorozhsky earthquake has been carried out. The problems of improvement the earthquake representative estimate for the eastern part of Ukraine have been formulated.